A Route to Stereochemically Pure Benzyllithium Reagents by Stereocontrolled Epimerisation. Issue 2 (18th November 2014) - Koller, Stephan G.; Kroesen, Ulrike; Strohmann, Carsten
Abstract Alkyllithium compounds are not generally stable at room temperature, therefore strategies were established to overcome this limitation. We present a systematic approach to obtain a stereochemically enriched benzyllithium compound, starting with the simple addition of a chiral auxiliary and ending by incorporation of the auxiliary in the substrate. Thereby, a very unusual dimer of a lithiated benzylsilane was obtained, which could be split into stereochemically enriched monomers by the addition of Lewis bases. Furthermore, we were able to understand the factors responsible for this stereochemical enrichment by using quantum chemical calculations and clarify the configuration of the lithiated compound and the corresponding trapping product by crystallisation. This enabled us to determine the stereochemical course of the deprotonation and the subsequent metathesis reaction.